Psychological interventions to improve psychological well-being in people with dementia or mild cognitive impairment: systematic review and meta-analysis protocol. Issue 1 (27th January 2016) - Farrand, Paul; Matthews, Justin; Dickens, Chris; Anderson, Martin; Woodford, Joanne
Abstract : Introduction: Dementia and mild cognitive impairment are associated with an increased risk of depression, anxiety, psychological distress and poor mental health-related quality of life. However, there is a lack of research examining the evidence base for psychological interventions targeting general psychological well-being within this population. Furthermore, there is little research relating to the design of randomised controlled trials examining psychological interventions for dementia and mild cognitive impairment, such as effective recruitment techniques, trial eligibility and appropriate comparators. Methods and analysis: Systematic review of electronic databases (CINAHL; EMBASE; PsychInfo; MEDLINE; ASSIA and CENTRAL), supplemented by expert contact, reference and citation checking, and grey literature searches. Published and unpublished studies will be eligible for inclusion with no limitations placed on year of publication. Primary outcomes of interest will be standardised measurements of depression, anxiety, psychological distress or mental health-related quality of life. Eligibility and randomisation proportions will be calculated as secondary outcomes. If data permits, meta-analytical techniques will examine: (1) overall effectiveness of psychological interventions for people with dementia or mild cognitive impairment in relation to outcomes of depression, anxiety, psychological distress or mental health-related quality of life; (2) clinical and methodological moderators associated with effectiveness; (3) proportions eligible, recruited and randomised. Ethics and dissemination: Ethical approval is not required for the present systematic review. Results will inform the design of a feasibility study examining a new psychological intervention for people with dementia and depression, with dissemination through publication in peer-reviewed journals and presentations at relevant conferences. Trial registration number: CRD42015025177.